Sui lirici greci nelle Operette Morali: ‘affioramenti’, citazioni, affinità - Favaro, Francesca (Rivista Internazionale di Studi Leopardiani, 2024)
The essay aims to examine the presence of Greek lyricists in Leopardi’s Operette morali. In some cases this presence is realized through explicit quotations; more often, however, it corresponds to a suggestion, an allusion, an affinity. In this contribution I focus on the revivals and ‘unveilings’ of the poets Anacreon, Pindar and Semonides within the varied dialogic fabric of the Leopardi sylloge.